2021
DOI: 10.1097/md.0000000000027864
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prognostic metabolic genes in adrenocortical carcinoma and establishment of a prognostic nomogram

Abstract: Adrenocortical carcinoma is an invasive malignancy with poor prognosis, high recurrence rate and limited therapeutic options. Therefore, it is necessary to establish an effective method to diagnose and evaluate the prognosis of patients, so as to realize individualized treatment and improve their survival rate.This study investigated metabolic genes that may be potential therapeutic targets for Adrenocortical carcinoma (ACC). Level 3 gene expression data from the ACC cohort and the relevant clinical informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Our results showed statistical difference between two groups but the AUC value was relatively low, suggesting that CYP11B1 had potential for distinguishing carcinomas from adenomas. Additionally, Qing Chen et al [ 23 ] reported the identification of a CYP11B1 signature in ACCs and its prognostic value. However, our study showed no prognostic significance of CYP11B1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed statistical difference between two groups but the AUC value was relatively low, suggesting that CYP11B1 had potential for distinguishing carcinomas from adenomas. Additionally, Qing Chen et al [ 23 ] reported the identification of a CYP11B1 signature in ACCs and its prognostic value. However, our study showed no prognostic significance of CYP11B1.…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 is a classical marker that reflects the activity of cell proliferation and is widely used in various tumors. ACC, as a proliferation-driven malignancy, typically displays a Ki-67 labeling index greater than 5%, which significantly exceeds that of ACA [ 3 , 5 , 23 ]. Notably, ACCs exhibit proliferative heterogeneity, requiring the accurate identification of hot spots to precisely assess the Ki-67 labeling index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study rigorously analyzes the efficacy of surgical interventions for DLSS, focusing on pain relief, functional outcomes, and operative time. In contrast, Chen et al [ 26 ] delve into the genomic landscape of Adrenocortical carcinoma (ACC), targeting metabolic gene signatures for prognostic evaluation. These distinct studies underscore different clinical challenges, rendering direct comparisons non-applicable, and emphasizing the breadth of ongoing medical research.…”
Section: Discussionmentioning
confidence: 99%